1988
DOI: 10.3109/00207458808985779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daytime Noise Load on the Sleep-Wake Cycle and Endocrine Patterns in Man. III. 24 Hours Secretion of Free and Sulfate Conjugated Catecholamines

Abstract: This study was designed to re-examine the circadian profiles of dopamine, noradrenaline and adrenaline in the plasma and to investigate the influence of daytime noise stress on these profiles. Twelve subjects participated in two experimental series of 60 h; during one they were exposed to 85 dB(A) industrial noise from 9:00 to 21:00 h. Blood samples were taken for a period of 24 h at 20 min intervals and the plasma levels of the free and the sulfoconjugated catecholaminergic compounds were simultaneously measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Thus, in the current experiment, the decrease of sympathetic nervous tone to the skin of the extremities during the night-time might have not been greater with Type H clothing. Fruhstorfer et al (1988) have demonstrated that daytime stress induced a greater decrease of adrenaline during the sleep period. This might account for the lack of significant difference in the range of circadian oscillation of rectal temperature between the two clothing types (Table I), and accords with our previous finding (Park & Tokura 1998) that the evening fall of rectal temperature was significantly and positively correlated with the decrease of adrenaline at this time.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, in the current experiment, the decrease of sympathetic nervous tone to the skin of the extremities during the night-time might have not been greater with Type H clothing. Fruhstorfer et al (1988) have demonstrated that daytime stress induced a greater decrease of adrenaline during the sleep period. This might account for the lack of significant difference in the range of circadian oscillation of rectal temperature between the two clothing types (Table I), and accords with our previous finding (Park & Tokura 1998) that the evening fall of rectal temperature was significantly and positively correlated with the decrease of adrenaline at this time.…”
Section: Discussionmentioning
confidence: 97%
“…1996; Park & Tokura 1998). These reports suggest that the stress of some factors (noise, light, and temperature stimulus) during daytime affected the night‐time epinephrine dynamics, which are related to core body temperature (Åkerstedt & Fröberg 1979; Fruhstorfer et al . 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The catecholamines were assessed according to Frustorfer et al [2], histamine according to Lorenz et al [4], complement-C5a and interleukin-6 with commercially available kits (Enzygnost ® C5a micro, Behringwerke AG, and Quantikine ® High Sensitivity Assay, R & DSystems).…”
Section: Methodsmentioning
confidence: 99%